TGF-β1 Promotes Autophagy and Inhibits Apoptosis in Breast Cancer by Targeting TP63 - Wang, Yichao; Lu, Hongsheng; Wang, Zhongrong; Li, Yueguo; Chen, Xiaoying (Frontiers in Oncology, 2022)
Background: Breast cancer (BC) is a prevalent female cancer, which has high morbidity and mortality. However, the pathogenesis of BC has not been fully elucidated. Studies have shown that TGF-β1 plays an important role in regulating the balance between autophagy and apoptosis of tumor. We aim to clarify the specific mechanism of autophagy and apoptosis in breast cancer maintaining the tumor microenvironment. Methods: The clinical characteristics of 850 BC patients were retrieved from the TCGA database. Differentially expressed autophagy-related genes (DEARGs) between tumor and normal tissues were obtained by the Wilcox test. Through Cox proportional hazard regression analysis, the prognostic risk model was constructed and verified by the ROC curve. We used MDC staining, colony formation assay, CCK-8, flow cytometric analysis to confirm the importance of TGF-β1 on the autophagy and apoptosis of breast cancer cells. Furthermore, western blot was performed to determine the relative expression of protein. The Kaplan-Meier Plotter database was utilized to identify the prognostic value of TP63. Results: We successfully constructed a prognostic risk model of breast cancer and screened out an autophagy-related prognostic gene -TP63. We predicted that TGF-β1 and TP63 have a binding site in the JASPAR database as expected. Additionally, TGF-β1 promoted autophagy and inhibited apoptosis of breast cancer cells by inhibiting the expression of TP63. Conclusion: Our study demonstrated that the molecular mechanism of TGF-β/TP63 signaling in regulating autophagy and apoptosis of breast cancer and provided a potential prognostic marker in breast cancer.